TAUBAT DALAM PANDANGAN ISLAM DAN KRISTEN - Arifinsyah Arifinsyah; Fitriani Fitriani; Isya Intan Fauzi (Studia Sosia Religia, 2022)
Religion is a guide for every human being to live life by following good and right rules, even so there will always be humans to choose the wrong path and result in sin, to erase the sins that have been committed, humans must repent. The purpose of this study is to increase knowledge about the meaning of repentance in Islam and Christianity, then to find out how to repent correctly according to Islamic and Christian teachings, and are there similarities and differences between repentance in Islam and Christianity. The method used in this research is qualitative with a literature study research design. This research can produce knowledge and understanding that previously a person has committed a sin, then he can change himself and repent after understanding the true meaning of how sin is and how to repent according to the guidance of Islam and Christianity.